Servant leadership and innovative work behavior: Does psychological empowerment matter? - Mercy Wanyana; Ibrahim Abaasi Musenze; Kaziba Abdul Mpaata (Taylor & Francis Group, 2026)
Using the social exchange theory and Spritzer’s empowerment model, this research explains how servant leadership affects innovative work behavior. There is a lack of empirical evidence on servant leadership’s influence on innovative behavior within the African or higher education context, as well as mediating models of psychological empowerment in the relationship between servant and innovative work behavior. The present study particularly hypothesizes that psychological empowerment positively mediates the Servant Leadership-Innovative Work Behavior relationship. To examine the proposed links, using a cross-sectional survey, the study uses a sample of 308 academic staff members employed by Uganda’s public universities. The findings derived from the structural equation modeling validate each of the study’s hypotheses and suggest new research directions of inquiry for servant leadership and innovative work behavior research. Specifically, servant leadership predicted innovative work behavior, and psychological empowerment significantly mediated the relationship between servant leadership and innovative work behavior. The present study clarifies the hitherto understudied relationship between servant leadership and employees’ innovative work behaviors in Uganda’s public universities, as well as the crucial role psychological empowerment plays in this relationship. This is an important finding for both theory and practice.
Keywords: innovative work behavior; servant leadership; psychologicalempowerment; structuralequation modeling; public universities